Design for community greenway - low maintenance trail for recreational and educational purposes at the Faculty Of Sustainable Agriculture, UMS Sandakan - Ooi, Pei Ning (Faculty Of Sustainable Agriculture, 2016)
This study was conducted from February 2015 to November 2015 (28 weeks) to explore greenway landscape planning at the Faculty of Sustainable Agriculture, Universiti Malaysia Sabah Sandakan Campus (geographical coordinates: 500 55' 51.32"" N, 1180 00' 39.92"" E), Sandakan. This study aimed to promote a healthy campus life in Faculty of Sustainable Agriculture (FSA) as well as to improve the well-being of its community. The study site was located at the main lake of FSA, which is also the largest lake in FSA. The objectives of this research were to assess FSA's community's input on the idea of a multifunctional trail in the campus and their knowledge on sustainable landscape practices, conduct site inventory and analysis at the proposed site and recommend a lowmaintenance trail design. This thesis employed a mixed-method approach which were qualitative method (site inventory and site analysis) and quantitative method (questionnaire survey and descriptive statistical analysis). The existing soil was extremely dry and the pH range from 6.2 to 8. Questionnaire were distributed to 50 respondents and the findings collected were analysed and utilized for the design recommendation at the proposed site. Based on the findings, there were 86% respondents who were unsatisfied with the existing site and 72% was not familiar with application of sustainable landscape practices. The proposed site was divided into four different zones: Zone A, Zone B, Zone C and Zone D. The final output of the landscape design recommendation were master plan, several perspectives from each zone and planting palette. To conclude, a low-maintenance landscape, which integrated with greenway concept and sustainable practices, was proposed to be implemented at the lakeside of FSA, which mainly included low-maintenance (concrete-based) trail and lowmaintenance plants along the lakeside for recreational and educational purposes.